2009
DOI: 10.1039/b822684a
|View full text |Cite
|
Sign up to set email alerts
|

Towards a molecular-level understanding of the reactivity differences for radical anions of juglone and plumbagin: an electrochemical and spectroelectrochemical approach

Abstract: An electrochemical and spectroelectrochemical strategy is presented for evaluating reactivity differences in the semiquinone anions from naturally occurring quinones juglone (5-hydroxy-1,4-naphthoquinone) and plumbagin (2-methyl-5-hydroxy-1,4-naphthoquinone). By employing cyclic voltammetry and in situ spectroelectrochemical electron spin resonance measurements, it was found that while semiquinone species generated from plumbagin are stable radical anions in DMSO solution, the species generated from juglone ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…These latter species are involved in self‐protonation process involving a slow rate of protonation due to the mild acidity of the hydroxyl group at the C‐5 position. This result is important when considering observed differences in biochemical reactivity for these quinones, particularly in cases where mediated cytotoxic action is provoked by these agents . The electrochemical behavior of plumbagin has been studied in nonaqueous solvents by cyclic voltammetry, chronoamperometry, and chronopotentiometry, using Au, Pt, glassy carbon electrodes, tetraethylammonium pe0roxydicarbonate, and tetrabutylammonium perchlorate as supporting electrolytes.…”
Section: Spectral and Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These latter species are involved in self‐protonation process involving a slow rate of protonation due to the mild acidity of the hydroxyl group at the C‐5 position. This result is important when considering observed differences in biochemical reactivity for these quinones, particularly in cases where mediated cytotoxic action is provoked by these agents . The electrochemical behavior of plumbagin has been studied in nonaqueous solvents by cyclic voltammetry, chronoamperometry, and chronopotentiometry, using Au, Pt, glassy carbon electrodes, tetraethylammonium pe0roxydicarbonate, and tetrabutylammonium perchlorate as supporting electrolytes.…”
Section: Spectral and Electrochemical Propertiesmentioning
confidence: 99%
“…This result is important when considering observed differences in biochemical reactivity for these quinones, particularly in cases where mediated cytotoxic action is provoked by these agents. 44 The electrochemical behavior of plumbagin has been studied in nonaqueous solvents by cyclic voltammetry, chronoamperometry, and chronopotentiometry, using Au, Pt, glassy carbon electrodes, tetraethylammonium peroxydicarbonate, and tetrabutylammonium perchlorate as supporting electrolytes. In aprotic solvent, such as acetonitrile, the compound exhibits two one-electron redox peaks due to the reversible charge transfers without a coupled chemical reaction, while in dichloromethane solvent, it shows two one-electron quasi-reversible peaks.…”
Section: Spectral and Electrochemical Propertiesmentioning
confidence: 99%
“…The presence of a 5-hydroxyl group for plumbagin does not affect the reversibility and the shape of the two one-electron reduction processes, which indicates that these ionizable substituents are not acidic enough to protonate the two reduced species. In addition, the intramolecular hydrogen bonding [72][73][74][75] stabilizes the negative charge of the reduced species and renders these derivatives more oxidant than menadione.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Allelopathic potential of this walnut constituent leads to inhibition of seed germination and growth of susceptible acceptor plants [6–10]. Detrimental impact of this naphthoquinone may be associated with suppressing the intensity of a wide range of physiological processes and biochemical reactions occurring in plant tissues [9,11,12]. It has been reported that juglone is responsible for reducing chlorophyll content [13], disrupting root plasma membrane and decreasing of water uptake [14], inhibition of photosynthesis, transpiration, respiration and stomatal conductance [15,16].…”
Section: Introductionmentioning
confidence: 99%